P222 Follow up of patients diagnosed with occupational asthma or rhinitis at royal brompton hospital. (15th November 2017) - Feary, J; Cannon, J; Schofield, S; Cullinan, P
Abstract : Background: Occupational asthma (OA) is common with c.15% of cases of new or relapsed adult asthma attributed to work. The lifetime cost of a diagnosis is estimated to be £100 million and is largely borne by the patient – who may need to change their job with subsequent loss of earnings – and the State. 1 We sought to understand changes in symptoms over time and the impact of a diagnosis of OA or occupational rhinitis (OR) on patients attending our clinic. Methods: Twelve months after diagnosis we sent a postal questionnaire to all patients with occupational rhinitis (OR) or asthma (OA) seen in the Royal Brompton Hospital Occupational Lung Disease. Reminders were sent on one occasion. We present responses from the first 100 completed questionnaires. Results: 73 respondents had OA (response rate 61%) and 27 OR (response rate 39%). 68% of all respondents were male; mean age was 44 years (SD 10.6). Of those with OA, 24 (33%) were bakers and 19 (25%) laboratory animal workers; 29% were in other manual jobs and 13% were in other non-manual jobs. Occupational groups were similar for those with OR but with a higher proportion of laboratory animal workers (38%) and fewer other manual workers (11%). The majority (83%) of patients were referred to our clinic from Occupational Health services. Most patients, especially those with OR, reported fairly rapid improvement in their condition once removed from exposure although many of those with OA reported consequent difficulties with careers and incomes (table ). Overall, almost all patients (OA 87%; OR 93%) claimed that they were 'glad' that their diagnosis had been recognised. Conclusions: Prognosis is generally good for patients attending our clinic with most reporting an improvement in their symptoms after diagnosis. Early diagnosis and removal from exposure is known to result in a better prognosis; health care professionals need to have a low threshold for suspecting OA so that patients can be identified early. Reference: Ayres JGet al. Thorax2011;66(2):128–33.